2015
DOI: 10.1016/j.ijgo.2015.04.045
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional sonography-based automated volume calculation (SonoAVC) versus two-dimensional manual follicular tracking in in vitro fertilization

Abstract: Three-dimensional SonoAVC could be a useful adjunct for follicular monitoring, with a significant reduction in time and a good correlation with manual counts. However, further studies with larger sample sizes are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…The results showed that the use of 3D SonoAVC did not lead to an improvement in cycle parameters. Previous studies [7][8][9][10][11][12][13] have demonstrated that SonoAVC is an effective and more accurate method of measuring follicular volume and diameter than real-time 2D techniques, and the process reduces the time required for the sonographic examination. Others 14,17,18 reported that 3D SonoAVC may influence the oocyte maturation rate because it provides data that allow clinicians to time oocyte retrieval according to the follicular volume in addition to the mean follicular diameter.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results showed that the use of 3D SonoAVC did not lead to an improvement in cycle parameters. Previous studies [7][8][9][10][11][12][13] have demonstrated that SonoAVC is an effective and more accurate method of measuring follicular volume and diameter than real-time 2D techniques, and the process reduces the time required for the sonographic examination. Others 14,17,18 reported that 3D SonoAVC may influence the oocyte maturation rate because it provides data that allow clinicians to time oocyte retrieval according to the follicular volume in addition to the mean follicular diameter.…”
Section: Discussionmentioning
confidence: 99%
“…The program identifies and quantifies hypoechoic regions within the 3D data set (Figure ), provides an automatic estimation of their absolute volumes, and calculates back from each volume to the mean diameter of each follicle . Measurements of follicular diameter and volume with SonoAVC were found to be more valid and accurate than those made with conventional 2D sonography . Furthermore, the individualized color code for each hypoechoic area eliminates the possibility of measuring the same follicle more than once.…”
mentioning
confidence: 99%
See 3 more Smart Citations